Discursos socialistas na educação brasileira (1959-1961) : marcas na elaboração da primeira LDBEN - Leite, Guilherme Nikolof (2021)
The drafting of the first national education guidelines and bases law (LDBEN) involved the clash between different currents and their representations about society, in addition to the development of an educational system. Among the different currents present in this debate are the socialists, represented both by the Communist Party of Brazil (PCB), as well as by educators identified with Marxism, different unions and social movements. These socialists actively contributed to the struggle for the public school, opposing greater privileges for the owners of private institutions. In their speeches, they used the achievements in the educational field in socialist countries to demonstrate this system as an imminent historical process and capable of providing greater achievements than any capitalist model. Thus, the central object of this research is to highlight the marks of the speeches produced by the socialists in the process of elaborating the LDBEN (nº 4,024 / 61) between 1959 and 1961, when the substitute 2,222 / 57 was continued in the congress. This research has as sources of analysis some articles extracted from the party journal Novos Rumos (NR) and the educational Revista Brasileira de Estudos Pedagógicos (RBEP), through which it is possible to establish the centrality of education with the opportunity opened by the guidelines and bases for this process of social transformation. The methodology uses a post-structuralist perspective based on the indiciary technique and guided by the principles of Discursive Textual Analysis. In conclusion, it is possible to demonstrate that certain marks that identify socialists are precisely the organization of workers and students to carry out actions in favor of changing the meanings implicit to the substitute, resulting in the alteration of some articles in the law sanctioned in 1961.